Simulated moving bed adsorptive reactor: modeling, simulation and operation of a SMBR pilot plant - Pais, Luís S. (2010)
Adsorptive separations are becoming increasingly important in chemical industry. The simulated moving bed technology (SMB) developed by UOP has been used for various separations, namely the recovery of p-xylene from a mixture of C8 isomers (PAREX) or the separation Glucose/Fructose in the SAREX process. More recently flue technology has been introduced in the area of tine chemicals and pharmaceuticals by leading companies SEPAREX and UOP